Does capital market liberalization promote ESG disclosure? Empirical evidence from the mainland-HK stock connect - Nie, Mingjian; Chen, Changyu; Song, Chang; Qin, Chao (Frontiers in Environmental Science, 2023)
With the growing popularity of environmental, social, and governance (ESG), ESG performance is becoming increasingly important in investors’ decisions about firms. Capital market liberalization brings in more sophisticated and mature foreign investors who are more interested in corporate ESG performance. We investigate whether capital market liberalization improves corporate ESG disclosure using Shanghai-Hong Kong Stock Connect and Shenzhen-Hong Kong Stock Connect as exogenous shocks. By compiling a comprehensive dataset of Chinese A-share listed firms from 2006 to 2019 and manually calculating the ESG disclosure score, we find that the mainland-HK Stock Connect scheme enhances corporate ESG disclosure. This effect is heterogeneous for firms with different external environments, corporate characteristics, and environmental performance. The results suggest that the competition effect dominates the role of capital market liberalization in improving ESG disclosure of mainland listed firms and firms disclose their ESG practices to cater to the need of investors. This paper enriches the empirical research on the impact of capital market liberalization on firm behavior and performance and provides a theoretical basis for strengthening regulations in ESG information disclosure.